The effect of stakeholder on firm value and environmental performance as intervening variable - Djoko Suhardjanto; Sigit Santosa; Tri Fitrianto Suratno; Rini Fatmawati (Jurnal Akuntansi, Keuangan, dan Manajemen, 2021)
Purpose: This study aimed to understand the relationship between stakeholder and firm value with environmental performance as the intervening variable. The study was conducted on companies listed in Indonesia Stock Exchange and listed in the PROPER program during 2016 and 2017. The stakeholder variables in this study consist of managerial ownership (manager), consumer, and employee. Research methodology: The samples were determined using purposive sampling with a total of 131 companies and using path analysis method as an expansion of regression analysis. Result: The result is managerial ownership, consumer, and employee do not affect firm value directly. Managerial ownership has a positive and significant effect on firm value through environmental performance. The consumer has a significant and negative effect on the firm value through environmental performance and employee has a significant and negative effect on the firm value. Limitation: The sample is limited for two years period and adjusted R2 is 21.5%. Contribution: This study can identify variables that affect firm value, especially: manager, consumer, employee and environmental performance. Keywords: Firm value, Stakeholder, Environmental performance